2023
DOI: 10.3390/s23104661
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation of the Dorsolateral Prefrontal Cortex Increases Posterior Theta Rhythm and Reduces Latency of Motor Imagery

Abstract: Experiments show activation of the left dorsolateral prefrontal cortex (DLPFC) in motor imagery (MI) tasks, but its functional role requires further investigation. Here, we address this issue by applying repetitive transcranial magnetic stimulation (rTMS) to the left DLPFC and evaluating its effect on brain activity and the latency of MI response. This is a randomized, sham-controlled EEG study. Participants were randomly assigned to receive sham (15 subjects) or real high-frequency rTMS (15 subjects). We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The authors of [ 45 ] used a memory retrieval task to demonstrate that an increase in prestimulus theta activity can be associated with better source memory accuracy. Another research [ 46 ] showed high posterior theta-band power occurring in the time interval between the cue and the formation of ERD in a motor imagery task, which the authors hypothesized was related to the cue processing. The authors also linked this observation to a widely reported negative correlation between theta-band power and default mode network (DMN) activation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [ 45 ] used a memory retrieval task to demonstrate that an increase in prestimulus theta activity can be associated with better source memory accuracy. Another research [ 46 ] showed high posterior theta-band power occurring in the time interval between the cue and the formation of ERD in a motor imagery task, which the authors hypothesized was related to the cue processing. The authors also linked this observation to a widely reported negative correlation between theta-band power and default mode network (DMN) activation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The idea is to modulate neural circuits related to attention and executive functions to improve cognitive performance. Targeted stimulation: Researchers studied the effects of TMS on specific brain regions involved in attention, such as the dorsolateral prefrontal cortex [ 88 , 89 ]. The goal of delivering magnetic pulses to these areas is to enhance neural activity and potentially improve attentional processes.…”
Section: Clinical Applications: Tms For Adhd and Depressionmentioning
confidence: 99%
“…Various studies revealed that MI, AO and motor execution (ME) approximately share the same neural networks activated during motor performance (Crammond, 1997;Grèzes and Decety, 2001;Jeannerod, 2001;Hardwick et al, 2018) as demonstrated by evidences coming from preclinical researches in neurophysiology (Fleming et al, 2010;Hardwick et al, 2018;Kurkin et al, 2023) together with results of human experiments carried out with transcranial magnetic stimulation and functional MRI.…”
Section: Introductionmentioning
confidence: 99%